Transient Analysis of Queueing Model - Sah, Shyam Sundar; Ghimire, Ram Prasad (Journal of the Institute of Engineering, 2016)
This paper deals with the study of Erlangian queueing system with time dependent framework. Under our study we fnd (i) the expected number of customers in the queue (ii) the expected waiting time before being served (iii) the expected time spent in the system (iv) the expected number of customers in the system. Customers arrive in the system in Poisson fashion with rate  and served in arbitrary service time distribution with rate µ.The probability generating function technique and Laplace transform method have been used. The numerical computation has also been obtained for applicability of the model. Journal of the Institute of Engineering, 2015, 11(1): 165-171